SPECTROPHOTOMETRÄ°C STUDY OF THE COMPLEX FORMATÄ°ON OF COPPER (II) WÄ°TH 1-PHENYL-2- [2-HYDROXY-3-SULFO-5-NÄ°TROPHENYLAZO] 1,3-BUTADÄ°ONE Ä°N THE PRESENCE OF CATÄ°ONÄ°C SURFACTANTS. - Ðyvazova, Ð. V.; Aliyeva, R. A.; Chiragov, F. M.; Lahicova, S. R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Based on benzoylacetone synthesized 1-phenyl-2- [2-hydroxy-3-sulfo-5-nitrophenylazo] 1,3-butadione (PHSNPAB). Studied complex formation of copper (II) with 1-phenyl-2- [2-hydroxy-3-sulfo-5-nitrophenylazo] 1,3-butadione (PHSNPAB) in the presence and absence of the third component such as cetylpyridinium chloride (CPCl), cetylpyridinium bromide (CPBr) and cetyltrimethylammonium bromide (CTMABr). Single ligand complexes are formed at pH = 3, Î» = 444nm, and mixed ligand complexes at pH = 2 Î» = 456, 454, and 461 nm, respectively (CPCl, and CPBr, CTMABr). Ä°dentified the relations of the reacting components in homogeneous composition of Cu-R (1: 2) and mixed ligand Cu-R-CPCl (1: 2: 2), Cu-R-CPBr (1: 2: 2) and Cu-R-CTMABr (1 2: 1) complexes, which concentration interval subordinated to Beer’s law. The influence of external ions and masking substances on complex formation was studied. Method for the photometric determination of copper in the rocks was established.